VI Meeting of the Technical Advisor Committee of Plan Protection Directors. Caribbean Area - Ambrose, Everton (IICA, 2021)
This document presents: development of the meeting, IICA reports, technical papers, country papers, meeting of the plant protection directors in the OECS.